2012
DOI: 10.1002/tal.588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seismic behaviour of steel special moment frame buildings with vertical irregularities

Abstract: This paper concentrates on investigating the seismic behaviours of vertically irregular steel special moment frame (SMF) buildings by comparison with the regular counterpart. All buildings in this study were assumed to be located in Los Angeles, and subjected to 20 earthquake ground motions with a seismic hazard level of 2% probability of exceedance in 50 years. The beam–column connections of the buildings were modelled to consider the panel zone deformation. In addition, a ductile connection model accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…In general, fire resistance is defined as a period of time during which the integrity of the structure is kept reasonably intact so that it can support the applied gravity loads without collapse (Kodur and Dwaikat, ). While previous studies have confirmed that earthquake‐damaged structures are more vulnerable to fire than intact structures, it is deemed that this vulnerability would even be more in irregular structures (Le‐Trung et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, fire resistance is defined as a period of time during which the integrity of the structure is kept reasonably intact so that it can support the applied gravity loads without collapse (Kodur and Dwaikat, ). While previous studies have confirmed that earthquake‐damaged structures are more vulnerable to fire than intact structures, it is deemed that this vulnerability would even be more in irregular structures (Le‐Trung et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 As per UBC, 3 a building is said to be irregular in mass if the effective mass of a storey or storeys is more than 150% of the effective mass of the neighboring adjacent storeys. Mass-irregular building frames have been reported to have resulted into greater seismic response (and hence critical) as compared to regular counterparts, when excited by the same earthquake force (see, e.g., Choi and Le-Trung et al 2,4 ). Irregularity in storey mass may arise due to variation in floor use patterns, for example, residential, parking, commercial/shopping, and heavy machinery floors, or due to conversion of existing floor(s) use, for similar requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, elastic component of deformation has been found to be uniform throughout the building height, whereas inelastic component has been observed to concentrate at the lower storeys (i.e., within 25% to 45% building height). Le-Trung et al 4 investigated the seismic behavior in terms of both seismic demand and seismic capacity of 20-storey mass-irregular steel moment-resisting frames by performing NTHA using conventional FE-based program DRAIN-2DX. Single-floor mass irregularity located at two locations (i.e., 5% and 100% building height) has been considered in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…They performed nonlinear dynamic analysis on 6 prototype buildings and concluded that the irregularity has a significant effect on the nonlinear response and lateral stability of the structures under earthquake. Seismic performance of vertically irregular steel moment frames were studied by Lee et al [8]. Their results showed that presence of higher mass at higher stories can cause larger story drifts for the entire building.…”
Section: Introductionmentioning
confidence: 99%